Control and Monitoring System for Lighting Through Timing Based on The Internet of Things - Putri, Maharani; Abdullah; Iriani, Juli; M. Syahruddin; Cholish; Guci, Putra Sawaluddin; Sembiring, Eme Aginta Br; Evalina, Noorly (MultiTech Publisher, 2024)
This study aims to develop and implement a time-based lighting control and monitoring system using the Internet of Things (IoT). In today's digitally connected environment, efficient lighting control is essential to improve user comfort and optimize energy use. The proposed approach leverages light sensors and IoT hardware to automatically adjust lighting levels based on time and user needs. The system is designed to provide users with the ability to control lighting remotely via a mobile application or web interface. In addition, the collected lighting data can be analyzed to understand lighting usage patterns and improve energy efficiency. The research methodology includes system design, hardware and software development, and implementation trials in a real environment. Testing was carried out by varying lighting scenarios and monitoring the system's response to these changes. The results showed that the system was able to optimize room lighting according to user preferences and environmental conditions efficiently. In addition, the remote monitoring and control capabilities provide greater flexibility for users to adjust lighting according to their needs. This study contributes to the field of time-based lighting control by utilizing the advantages of IoT as remote control and monitoring.